A Short Glance at the Role of Olfaction in Depression - Zhengwei Wen#; Chanyi Lu#; Hua-Zhen Lin#; Yao-Yao Li#; Yun-Feng Zhang (Archives of Depression and Anxiety - Peertechz Publications, 2017)
Depression  as  one  kind  of  neuropsychiatric  disorder  affects  tons  of  population  in  the world  and exerts great economic and social burden. Great efforts have been made during the past decades aiming to  decipher  the  underlying  mechanism  of  this  mental  disease.  Different  kinds  of  mechanisms  underlie depression, among which malfunctions in the olfactory system is one important reason. The occurrence of depression has a close association with dysfunctions in the olfactory system, which is highlighted by some brain regions responsible for depression overlapping with areas playing crucial roles in olfaction. The close relationship between olfactory malfunctions and depression is also underscored by the evidence that some patients with depression exhibited a higher probability of odor identification impairment and a reduced olfactory sensitivity as well as smaller olfactory bulb volumes. For reasons of concise and clarity,in the current review we only briefly summarized some key recent studies pertaining to the relationship between the dysfunctional olfaction and depression, to underscore potentially crucial roles of the normal olfactory system function in ameliorating the probability of the occurrence of depression.